The differential psychology applied to the students with low academic use - De la Torre Batista, Yanet; Parra Michel, Pastor; Chimbinda Samandjata, Bernice Nanjala (Espergesia, 2020)
The investigation that is presented, gives answer to a problem that interferes in the development of the learning in the school. It has as general objective: to analyze the particularities of the students with low academic use in the Primary School “Cato” in the city of Sumbe. To give answer to the theoretical premises about the topic in question starting from a qualitative - quantitative methodology with the use of theoretical, empiric and statistical methods that allowed to arrive to the following results: the treatment to the individual differences in the students with low academic use in this school is insufficient for a good learning of the same ones; this allowed to reach conclusions and to propose recommendations.